Communication and functioning of pupils with autism in public school three case studies - ZAJĄC, EWELINA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Ewelina Zając, Communication and functioning of pupils with autism in public school – three case studies. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 139-153. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.08 The purpose of this article is to characterize the means of communication of three autistic pupils with their teachers and peers as well as their daily functioning in the community of one of the public schools located in the Wielkopolska region of Poland.